Pendekatan dalam Memahami Matan Hadis (Double Movement Fazlurrahman) - Hilman, Muhamad Hasymi; Ummam, Naufal Izzul (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
The literal interpretation of hadith without historical and contextual analysis can lead to rigid, outdated understandings that risk marginalizing certain groups. This paper explores the hermeneutic method of double movement proposed by Fazlur Rahman as an alternative approach to interpreting hadith. The study aims to answer: how can Rahman’s method be applied to hadith texts, and what are its implications for contemporary Islamic thought? Using a qualitative library research method and descriptive-analytical approach, this research synthesizes various primary and secondary sources on hermeneutics and hadith methodology. Findings show that the double movement approach—moving from the present to the context of revelation and returning to the present—allows the recovery of the moral-ethical ideals embedded in hadith. Case studies, such as the prohibition on female leadership, demonstrate how contextual re-reading can result in more inclusive and just interpretations. This method proves essential for interpreting hadith in a way that remains relevant, moral, and intellectually engaging in modern contexts.